Dampak Kebijakan Zonasi Sekolah terhadap Kualitas Pendidikan di Wilayah Perkotaan - Ningtyas, Eryn Irsa; Karwanto, Karwanto; Amrozi Khamidi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze in depth the impact of school zoning policy on education quality in urban areas, focusing on the dynamics and challenges that arise in its implementation. The zoning policy, which was designed to realize equal access to education and reduce gaps between schools, has triggered significant changes in the education system. This study uses an extended qualitative descriptive approach, combining secondary data analysis from academic journals, government reports, and credible media, with multi-level discourse and policy analysis techniques to gain a comprehensive understanding. The results show that the zoning system has had a significant impact on equal access to education and student inclusiveness, but is still faced with various complex challenges such as inequality in school quality, community resistance, and unequal distribution of resources. Positive impacts identified include increasing student diversity, equal distribution of educational resources, and increasing parental involvement in education. However, negative impacts such as inequality in facilities between schools, difficulties in curriculum adaptation, and community dissatisfaction also emerged as important issues that need to be addressed. This study emphasizes the urgency of a comprehensive and integrated implementation strategy, which includes improving the quality of schools as a whole, equalizing the distribution of quality teachers, and effectively disseminating policies to all stakeholders. In addition, strong coordination between stakeholders is needed, including the government, schools, parents, and the community, as well as changing public perceptions about superior schools. The study, that zoning policies have great potential in realizing equal distribution of quality education if balanced with efforts to improve the quality of schools that are sustainable and targeted implementation strategies. Keywords: School Zoning Policy, Education Quality, Urban Areas